High-aluminum zinc-based wear-resistant alloy material and preparation method thereof

By using high aluminum -zinc -based wear -resistant alloy materials, using a star ball mill to grind SIC powder and copper, to form the covering effect of CU on SIC particles, and mix with the aluminum zinc solution under melting conditions to solve the abrasion resistance performance when the load friction is friction. The problem of decline has significantly improved the tensile strength, yield strength, and the hardness of the Book of materials.

CN119351852APending Publication Date: 2025-01-24SHAANXI DUOWEI XINJI IND MANUFACTURING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411461482.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In the prior art, there is a problem that wear resistance is degraded during load friction.

Method used

Using high aluminum -zinc -based wear -resistant alloy materials, synthetic raw materials include 48 % to 50.2 % aluminum, 1.3 % to 2.1 % of copper, 0.01 % to 0.02 % magnesium, 2.35 to 3 % SIC powder, and 0.1 % to 0.4 % of refinery, The amount is zinc. Gour the SIC powder and copper through the star mill to form the cover effect of the CU on the SIC particles, and mix it with the aluminum zinc solution under the melting conditions to mix and heat the heat to improve the wear resistance.

Benefits of technology

It has significantly improved the tensile strength, yield strength and the hardness of the BBC, enhanced the abrasion resistance, and can maintain good wear resistance in the load friction conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351852A_ABST
    Figure CN119351852A_ABST
Patent Text Reader

Abstract

The invention relates to a high-aluminum zinc-based wear-resistant alloy material and a preparation method thereof, and the high-aluminum zinc-based wear-resistant alloy material comprises the following components in percentage by mass: 42-44.2% of aluminum; 1.3%-2.1% of copper; 0.01% to 0.02% of magnesium; 2.35%-3% of SiC powder; 0.1%-0.4% of a refining agent and the balance of zinc. The preparation method comprises the following steps: firstly, grinding SiC powder and copper, then sequentially melting the raw materials of aluminum, zinc and magnesium, finally adding a SiC powder and copper mixture into an aluminum-zinc-based solution, stirring at a proper temperature, then carrying out the steps of degassing, deslagging, mold reversing, heat treatment, hardening and tempering and the like, and then cooling to room temperature, thereby completing the preparation of the wear-resistant alloy material. The high-aluminum zinc-based wear-resistant alloy material has the characteristics of high tensile strength, high yield strength, high Brinell hardness and good wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, and in particular to a high-aluminum-zinc-based wear-resistant alloy material and a preparation method thereof. Background Art

[0002] Wear-resistant materials refer to materials that can resist friction and wear fatigue under friction and wear environments. According to different application scenarios, wear-resistant materials can be divided into three categories: metal wear-resistant materials, non-metallic wear-resistant materials and composite wear-resistant materials. Wear-resistant materials are widely used in energy, transportation, chemical industry, metallurgy and other fields, such as coal-fired power generation, automobile engines, pipeline transportation and oil extraction. The hardness of wear-resistant materials is an important indicator to measure their ability to resist hard objects pressing into their surface. Generally speaking, the higher the hardness, the better the wear resistance.

[0003] In the prior art, products that require wear resistance, such as large bearings, sleeves, worm gears, and bearing retainers, usually generate load-bearing friction during use. During load-bearing friction, problems such as reduced wear resistance may occur. Summary of the invention

[0004] Based on this, it is necessary to provide a high aluminum zinc-based wear-resistant alloy material to address the above technical problems and effectively solve the problem of decreased wear resistance during load friction.

[0005] In a first aspect, the present invention provides a high aluminum zinc-based wear-resistant alloy material. The synthetic raw materials of the wear-resistant alloy material include the following components in terms of mass percentage:

[0006] Aluminum 48%~50.2%;

[0007] Copper 1.3% to 2.1%;

[0008] Magnesium 0.01% to 0.02%;

[0009] SiC powder 2.35-3%;

[0010] Refining agent 0.1%~0.4%

[0011] The balance is zinc;

[0012] The method for preparing the high aluminum zinc-based wear-resistant alloy material comprises the following steps:

[0013] S1: weigh the raw materials of each component according to the proportion, and preferentially weigh SiC powder and raw copper, with copper being powder;

[0014] S2: adding SiC powder and raw copper into a star ball mill and grinding for more than 20 hours;

[0015] S3: Weigh aluminum of the same mass as the raw material zinc, melt the raw material zinc and the same mass of aluminum in a crucible, and then cool them to obtain synthetic aluminum-zinc;

[0016] S4: Put the remaining aluminum and magnesium in the raw materials into the crucible, and after the remaining aluminum and magnesium are melted, put the synthetic aluminum zinc, and after the synthetic aluminum zinc is melted, put the mixed powder of SiC and copper ground in step S2, stir for more than 30 minutes, and press the refining agent into the metal solution under the melting temperature condition;

[0017] S5: after the liquid raw materials in the crucible are evenly mixed, the liquid mixture is degassed and deslagging;

[0018] Pour the degassed and deslagging liquid mixture into a mold, and spray water on the surface of the mold to cool the mixture in the mold to room temperature;

[0019] S6: demolding the mixture from the mold, performing heat treatment and tempering, and then cooling to room temperature to obtain a high aluminum zinc-based wear-resistant alloy material.

[0020] In one embodiment, in step S2, the grinding time is 20 to 22 hours, the rotation speed of the planetary ball mill is 300 to 350 rpm, and the ball-to-material ratio in the planetary ball mill is 20:1.

[0021] In one embodiment, in step S2, the grinding particle size of the mixed powder of SiC and copper is 2.3-3.1 μm.

[0022] In one embodiment, in step S4, the refining agent is silicon tetrafluoride.

[0023] In one embodiment, in step S4, the stirring time is 30 to 35 minutes, the stirring temperature is 480 to 550° C., and the stirring speed is 800 rpm.

[0024] In one embodiment, in step S6, the temperature of the heat treatment is 100°C to 180°C, and the duration is 1.5h to 2.5h.

[0025] The beneficial effects of the present invention are:

[0026] (1) The wear-resistant alloy material of the present invention mainly contains aluminum and zinc. First, SiC powder and raw copper are ground. Under the impact of ball milling, fine Cu is uniformly dispersed on the surface of SiC particles to form a Cu coating effect on SiC particles, which provides conditions for the subsequent infiltration of Cu and SiC coated particles into aluminum and zinc solutions under molten conditions.

[0027] (2) The appropriate stirring time of 30 to 35 minutes and the stirring temperature of 480 to 550°C make the particles of Cu and SiC coated particles more evenly dispersed in the aluminum and zinc matrix solutions, and the tensile strength, yield strength, Brinell hardness and other properties are greatly improved.

[0028] (3) The appropriate grinding particle size of the mixed powder of SiC and copper is 2.3-3.1 μm. The wear-resistant alloy material obtained has uniform particle distribution and fewer pores. In addition, since the Cu and SiC coated particles are dispersed inside the alloy, the SiC coated particles directly participate in the friction during the friction process, thereby enhancing the wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a SEM morphology image of SiC powder and copper mixture after grinding in Example 1 of the present invention;

[0030] Figure 2 This is a SEM morphology image of SiC powder and copper mixture after grinding in Example 2 of the present invention;

[0031] Figure 3 This is a SEM morphology image of the wear-resistant alloy material prepared in Example 1 of the present invention;

[0032] Figure 4 This is a SEM morphology image of the wear-resistant alloy material prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0033] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0035] A high-aluminum zinc-based wear-resistant alloy material. The synthetic raw materials of the wear-resistant alloy material include the following components by mass percentage: 48% to 50.2% aluminum; 1.3% to 2.1% copper; 0.01% to 0.02% magnesium; 2.35% to 3% SiC powder; 0.1% to 0.4% refining agent, and the balance is zinc.

[0036] The preparation method of the high aluminum zinc-based wear-resistant alloy material comprises the following steps:

[0037] S1: weigh the raw materials of each component according to the proportion, and preferentially weigh SiC powder and raw copper, with copper being powder;

[0038] S2: adding SiC powder and raw copper into a star ball mill and grinding for more than 20 hours;

[0039] S3: Weigh aluminum of the same mass as the raw material zinc, melt the raw material zinc and the same mass of aluminum in a crucible, and then cool them to obtain synthetic aluminum-zinc;

[0040] S4: Put the remaining aluminum and magnesium in the raw materials into the crucible, and after the remaining aluminum and magnesium are melted, put the synthetic aluminum zinc, and after the synthetic aluminum zinc is melted, put the mixed powder of SiC and copper ground in step S2, stir for more than 30 minutes, and press the refining agent into the metal solution under the melting temperature condition;

[0041] S5: after the liquid raw materials in the crucible are evenly mixed, the liquid mixture is degassed and deslagging;

[0042] Pour the degassed and deslagging liquid mixture into a mold, and spray water on the surface of the mold to cool the mixture in the mold to room temperature;

[0043] S6: demolding the mixture from the mold, performing heat treatment and tempering, and then cooling to room temperature to obtain a high aluminum zinc-based wear-resistant alloy material.

[0044] In step S2, the grinding time is 20 to 22 hours, the rotation speed of the planetary ball mill is 300 to 350 rpm, and the ball-to-material ratio in the planetary ball mill is 20:1.

[0045] In step S2, the mixed powder of SiC and copper has a grinding particle size of 2.3 to 3.1 μm.

[0046] In step S4, the refining agent is silicon tetrafluoride.

[0047] In step S4, the stirring time is 30 to 35 minutes, the stirring temperature is 480 to 550° C., and the stirring speed is 800 rpm.

[0048] In step S6, the temperature of the heat treatment is 100°C to 180°C, and the duration is 1.5h to 2.5h.

[0049] Among them, the refining agent is silicon tetrafluoride used to refine the alloy liquid. The main purpose is to remove the gas in the liquid metal and improve the density during aluminum-zinc hydraulic casting.

[0050] The following are specific embodiments.

[0051] Example 1

[0052] A high-aluminum zinc-based wear-resistant alloy material comprises the following components by mass percentage: 48% aluminum; 1.85% copper; 0.01% magnesium; 2.35% SiC powder; 0.1% refining agent; and the balance is zinc.

[0053] The preparation method comprises the following steps:

[0054] S1: weigh the raw materials of each component according to the proportion, and preferentially weigh SiC powder and raw copper, with copper being powder;

[0055] S2: SiC powder and raw copper were added to a star ball mill and ground for more than 20 hours, and the grinding particle size was 3.1 μm;

[0056] S3: Weigh aluminum of the same mass as the raw material zinc, melt the raw material zinc and the same mass of aluminum in a crucible, and then cool them to obtain synthetic aluminum-zinc;

[0057] S4: Put the remaining aluminum and magnesium in the raw materials into the crucible, and after the remaining aluminum and magnesium are melted, put in the synthetic aluminum zinc, and after the synthetic aluminum zinc is melted, put in the mixed powder of SiC and copper ground in step S2, stir for 30 minutes, the stirring temperature is 480°C, the stirring speed is 800 rpm, and the refining agent is pressed into the metal solution;

[0058] S5: after the liquid raw materials in the crucible are evenly mixed, the liquid mixture is degassed and deslagging;

[0059] Pour the degassed and deslagging liquid mixture into a mold, and spray water on the surface of the mold to cool the mixture in the mold to room temperature;

[0060] S6: demolding the mixture from the mold, performing heat treatment and tempering, and then cooling to room temperature to obtain a high aluminum zinc-based wear-resistant alloy material.

[0061] The high aluminum zinc-based wear-resistant alloy material in this embodiment was tested, and its tensile strength was 379 MPa, the yield strength was 315 MPa, and the Brinell hardness was 143 HB.

[0062] Example 2

[0063] A high-aluminum zinc-based wear-resistant alloy material, the other features of which are the same as those of Example 1, except that: in terms of mass percentage: aluminum 48.2%; copper 2.1%; magnesium 0.02%; SiC powder 3%; refining agent 0.4%; and the balance is zinc.

[0064] The preparation method is the same as that of Example 1, except that: S2: SiC powder and raw copper are added to a star ball mill and ground for 22 hours, and the grinding particle size is 2.3 μm;

[0065] S4: Stirring for 35 minutes, stirring temperature 550°C, stirring speed 800 rpm,

[0066] The wear-resistant alloy material in this embodiment was tested and found to have a tensile strength of 439 MPa, a yield strength of 336 MPa, and a Brinell hardness of 158 HB.

[0067] Compared with Example 2, the grinding particle sizes of SiC powder and copper mixture are 3.1 μm and 2.3 μm respectively; the smaller the size of the added mixture is, the more obvious the growth inhibition effect on other crystal phases in the composite aluminum and zinc alloy is, which is specifically manifested as follows: the smaller the size of the added mixture is, the more uniform the dispersion of Cu and SiC coated particles in the aluminum and zinc matrix solutions is, the fewer pores are, the smaller the size of the mixture is, the greater the Brinell hardness and tensile strength are, and the more wear-resistant it is; see Figure 1-4 ,in, Figure 1 and 2 The obvious white bright spots are Cu and SiC coated particles. Figure 3 and 4 The obvious white bright spots are Cu and SiC coated particles.

[0068] Compared with Example 2, Example 1 was stirred for 30 minutes at a stirring temperature of 480°C and stirred for 35 minutes at a stirring temperature of 550°C at a stirring speed of 800 rpm. The longer the stirring time and the higher the stirring temperature, the less the agglomeration of Cu and SiC coated particles, and the more uniformly they were dispersed in the aluminum and zinc matrix solution (the melting temperature of the aluminum and zinc matrix solution was about 430 degrees). In addition, since the Cu and SiC coated particles were dispersed in the alloy, the SiC coated particles directly participated in the friction during the friction process, thereby enhancing the wear resistance. Figure 1-4 ,in, Figure 1 and 2 The obvious white bright spots are Cu and SiC coated particles. Figure 3 and 4 The obvious white bright spots are Cu and SiC coated particles.

[0069] Comparative Example 1

[0070] The same test method was used to test the copper alloy wear-resistant material of model ZH59-1 in the prior art, and the tensile strength was 220-280 MPa, the yield strength was 200 MPa, and the Brinell hardness was 78.5-88.5 HB.

[0071] By comparing Examples 1 to 2 with Comparative Example 1, it can be seen that the tensile strength, yield strength and Brinell hardness of the wear-resistant alloy material of the present invention are greater than those of the copper alloy of model ZH59-1, and because the Cu and SiC coated particles are dispersed inside the alloy, the SiC coated particles directly participate in the friction during the friction process, thereby enhancing the wear resistance.

[0072] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A high aluminum zinc-based wear-resistant alloy material, characterized in that: The synthetic raw materials of the high aluminum zinc-based wear-resistant alloy material include the following components by mass percentage: Aluminum 48%~50.2%; Copper 1.3% to 2.1%; Magnesium 0.01% to 0.02%; SiC powder 2.35-3%; Refining agent 0.1%~0.4% The balance is zinc; The method for preparing the high aluminum zinc-based wear-resistant alloy material comprises the following steps: S1: weigh the raw materials of each component according to the proportion, and preferentially weigh SiC powder and raw copper, with copper being powder; S2: adding SiC powder and raw copper into a star ball mill and grinding for more than 20 hours; S3: Weigh aluminum of the same mass as the raw material zinc, melt the raw material zinc and the same mass of aluminum in a crucible, and then cool them to obtain synthetic aluminum-zinc; S4: Put the remaining aluminum and magnesium in the raw materials into the crucible, and after the remaining aluminum and magnesium are melted, put the synthetic aluminum zinc, and after the synthetic aluminum zinc is melted, put the mixed powder of SiC and copper ground in step S2, stir for more than 30 minutes, and press the refining agent into the metal solution under the melting temperature condition; S5: after the liquid raw materials in the crucible are evenly mixed, the liquid mixture is degassed and deslagging; Pour the degassed and deslagging liquid mixture into a mold, and spray water on the surface of the mold to cool the mixture in the mold to room temperature; S6: demolding the mixture from the mold, performing heat treatment and tempering, and then cooling to room temperature to obtain a high aluminum zinc-based wear-resistant alloy material.

2. A high aluminum zinc-based wear-resistant alloy material according to claim 1, characterized in that: In the step S2, the grinding time is 20 to 22 hours, the rotation speed of the planetary ball mill is 300 to 350 rpm, and the ball-to-material ratio in the planetary ball mill is 20:

1.

3. A high aluminum zinc-based wear-resistant alloy material according to claim 1, characterized in that: In the step S2, the grinding particle size of the mixed powder of SiC and copper is 2.3-3.1 μm.

4. The high aluminum zinc-based wear-resistant alloy material according to claim 1, characterized in that: In the step S4, the refining agent is silicon tetrafluoride.

5. The high aluminum zinc-based wear-resistant alloy material according to claim 1, characterized in that: In step S4, the stirring time is 30 to 35 minutes, the stirring temperature is 480 to 550° C., and the stirring speed is 800 rpm.

6. The high aluminum zinc-based wear-resistant alloy material according to claim 1, characterized in that: In step S6, the temperature of the heat treatment is 100° C. to 180° C., and the duration is 1.5 h to 2.5 h.